Pelatihan Guru Profesional bagi Guru SD/MI di Palangka Raya - Dian Lufia Rahmawati; Misyanto Misyanto; Agung Riadin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Community service aims to improve the professionalism of teachers in order to become a professional teacher and can advance the quality of education in Indonesia which is currently still relatively low quality. This devotion was held on Thursday, February 18, 2016, in the Hall Regional Chairman of Muhammadiyah Palangkaraya. Target communities in this devotion are the primary school teachers in the city of Palangkaraya, the selection of schools that follow the activities carried out at random/random. The method used in this service is to provide training to teachers in elementary school and later held discussions between participants and speakers. Cost of service activities is entirely sourced from Muhammadiyah University APBU Palangkaraya Year 2015. After the implementation of this activity, it can be concluded that the trainees acquire new knowledge or to refresh back the knowledge they already have.